PENINGKATAN HASIL BELAJAR IPS YANG KOMPREHENSIF MELALUI METODE SIMULASI DI MI NURUL ULUM MERTAK TOMBOK LOMBOK TENGAH - Hadi Wijaya; Mukminah Mukminah (JUPE : Jurnal Pendidikan Mandala, 2016)
This study aims to improve comprehensive learning outcomes of Social Studies through the application of the simulation method in Grade V of SD Muhammadiyah Bausasran ll Yogyakarta.This was a classroom action research study involving collaboration between the teacher and the researcher. The study was conducted in MI Darul Ulum Mertak Tombok Lombok Tengah and the research subjects were 29 Grade V students. The action implemented was the learning of Social Studies using the simulation method consisting of three cycles. The data were collected through tests, observations, interviews, and questionnaires. The research instruments were validated through expert judgment. The data were analyzed by means of the quantitative descriptive technique. The minimum mastery criterion applied at the school was a score of 65 for the cognitive, affective, and psychomotor aspects. The results of the study showed that the learning of Social Studies using the simulation method was capable of improving the learning outcomes of Social Studies in Grade V of MI Darul Ulum Mertak Tombok Lombok Tengah in the cognitive, affective, and psychomotor aspects. The improvements in the cognitive aspect in Cycles I, II, and III were, respectively, 62.06%, 75.86%, and 100%. The improvements in the affective aspect in Cycles I, II, and III were, respectively, 51.72%, 68.96%, and 75.86%. The improvements in the affective aspect in Cycles I, II, and III were, respectively, 41.38%, 75.86%, and 79.31%. Based on the results of the study, it can be concluded that the application of the simulation method is capable of improving comprehensive learning outcomes of Social Studies in Grade V of MI Darul Ulum Mertak Tombok Lombok Tengah. Therefore, teachers should apply the simulation method as an alternative to improve comprehensive learning outcomes of Social Studies